O-acyltransferase genes involved in the production of volatile sex pheromones in Caenorhabditis elegans - Xuan Wan; Sarah M. Cohen; Yan Yu; Henry Hoan Le; Heenam Park; Alessandro Groaz; Rachel Moreno; Minyi Tan; Jessica Schneider; Matthew R. Gronquist; Ryoji Shinya; Frank C. Schroeder; et al. (Proceedings of the National Academy of Sciences, 2026)
Gene family expansions are critical for functional diversification, yet the contributions of paralogs to metabolic pathways are often unclear. In Caenorhabditis , the expanded O-acyltransferase (OAC) family—enzymes that transfer acyl groups to hydroxylated substrates—remains poorly characterized despite having been implicated in lipid metabolism. Using CRISPR-Cas9 mutagenesis, behavioral assays, gas chromatographic-mass spectral (GC-MS) analyses, and metabolomics, we systematically analyzed 59 OAC-family protein-coding genes to define their roles in regulating signaling molecules. We found that four adjacent paralogs ( oac-13, oac-16, oac-25, and oac-28 ) on chromosome I are required for synthesizing volatile sex pheromones—airborne signals critical for male mate-searching. Specifically, oac -13 and oac-16 are necessary for producing both major pheromone components, while the identical tandem paralogs oac-25 and oac-28 regulate the production of the later-eluting component in gas chromatography. Disruption of these genes reduced production of key pheromone components and impaired male attraction. Metabolomics revealed that oac-16 and other OACs also modulate the synthesis and secretion of nonvolatile ascaroside pheromones, indicating dual roles in chemical signaling. This work uncovers functional specialization within an expanded gene family, illustrating how redundancy and divergence enable adaptive evolution of communication systems.